Behind the exporters' success - Kazai Onodi, Annamaria (Managing global transitions, 2014)
The purpose of the study is to provide an overview of export success from a strategic management perspective. The paper empirically tested the relationships between the firm's export performance, strategic thinking, adaptation to the changing environment and companies' capabilities. The research is based on the Hungarian Competitiveness Research database of 2013 that consists of 300 firms. Cluster analysis differentiated successful export-oriented and stagnant companies. Both of them had high export intensity (higher than 75%), but significant differences could be observed in export volume and profitability. More than 90% of total export revenue belonged to the successful export-oriented cluster. Successful exportoriented companies proved to be more proactive and innovative than stagnant, thus they were capable of adapting to the changing environment better. The study highlighted that appropriate strategic thinking could play a significant role in improving export success. The implication of the study is that stagnant companies need to develop their forecast abilities, flexibility to adapt to the changing environment and operational efficiency. Stagnant companies lagged behind successful exporters concerning industry forecast, production level, number of innovations, competitive prices and employee qualifications.
Keywords: internationalisation; podjetja; internacionalizacija; export; Hungarian Competitiveness Research Survey; izvoz; strategy; uspešnost; Hungary; Madžarska; konkurenčnost; strategija